2010
DOI: 10.1016/j.apnum.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of Boussinesq systems of the Bona–Smith family

Abstract: In this paper we consider the one-parameter family of Bona-Smith systems, which belongs to the class of Boussinesq systems modelling two-way propagation of long waves of small amplitude on the surface of water in a channel. We study numerically three initial-boundary-value problems for these systems, corresponding, respectively, to homogeneous Dirichlet, reflection, and periodic boundary conditions posed at the endpoints of a finite spatial interval. We approximate these problems using the standard Galerkin-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 58 publications
1
87
0
Order By: Relevance
“…Overtaking collision has been studied recently in the case of bidirectional models in [4]. The interaction is similar to that of the unidirectional models but it was found that a new N-shape wavelet is generated during the interaction.…”
Section: Overtaking Collisionsmentioning
confidence: 93%
See 2 more Smart Citations
“…Overtaking collision has been studied recently in the case of bidirectional models in [4]. The interaction is similar to that of the unidirectional models but it was found that a new N-shape wavelet is generated during the interaction.…”
Section: Overtaking Collisionsmentioning
confidence: 93%
“…These effects have been studied extensively before by numerical means using high order numerical methods such as finite differences, [11], spectral and finite element methods [4,27,62] and experimentally in [22]. In Fig.…”
Section: Head-on Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The travelling waves for the KdV-KdV systems were also studied numerically by Bona et al using unconditionally stable periodic splines Galerkin method with Gauss-Legendre implicit Runge-Kutta method of stage two [5]. Antonopoulos et al simulated the numerical solutions of three initial boundary value problems one parameter Bona-Smith systems [6]. The problems with homogenous Dirichlet, reflection, and periodic boundary conditions were integrated by Galerkin-finite element combined with fourth order explicit Runge-Kutta method.…”
Section: Boussinesq Systemsmentioning
confidence: 99%
“…A pseudo-spectral method was applied in [25], an implicit finite difference scheme in [53,7] and a compact higher-order scheme in [16,17]. Some Galerkin and Finite Element type methods have been successfully applied to Boussinesq-type equations [27,54,4,3]. A finite difference discretization based on an integral formulation was proposed by Bona & Chen [10].…”
Section: Introductionmentioning
confidence: 99%